KOMITMEN KEPALA MADRASAH DALAM MENINGKATKAN MOTIVASI KERJA GURU MADRASAH TSANAWIYAH PONDOK PESANTREN MODERN ACHMAD HATTA MUARO JAMBI - Anita, Putri; Musa; Sumirah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the issue of suboptimal teacher work motivation at Madrasah Tsanawiyah Pondok Pesantren Modern Achmad Hatta Muaro Jambi, as indicated by inconsistent discipline, limited participation in professional development activities, and differences in work enthusiasm between civil servant and non-civil servant teachers. The purpose of this study is to describe the principal’s commitment in improving teacher work motivation along with the supporting and inhibiting factors. This study uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings show that the principal enhances teacher motivation through exemplary leadership, spiritual and moral guidance, task distribution based on competencies, annual academic supervision, and encouraging teacher participation in MGMP and KKG every semester, along with providing rewards and efforts to improve teacher welfare. Supporting factors include a religious school environment and harmonious working relationships, while inhibiting factors involve differences in teacher status, limited facilities, and varied teacher competencies. Thus, teacher work motivation is strongly influenced by the principal’s commitment and leadership characterized by vision, effective communication, and role modeling.